Popular : vintage wisdom for a modern geek - Wagenen, Maya van. (2014)
"Stuck at the bottom of the social ladder at "pretty much the lowest level of people at school who aren't paid to be here," Maya Van Wagenen decided to begin a unique social experiment: spend the school year following a 1950s popularity guide, written by former teen model Betty Cornell. Can curlers, girdles, Vaseline, and a strand of pearls help Maya on her quest to be popular? The real-life results are painful, funny, and include a wonderful and unexpected surprise-meeting and befriending Betty Cornell herself. Told with humor and grace, Maya's journey offers readers of all ages a thoroughly contemporary example of kindness and self-confidence. "--
Keywords: Self-confidence -- Juvenile literature; Life skills -- Juvenile humor -- Juvenile literature; Teenage girls -- Juvenile literature; Life skills -- Juvenile literature